Driving Impairment Cases Involving Flualprazolam. Issue 7 (11th April 2022) - Youso, Kimberly B; Osawa, Kei A; Divine, Marina L; Rohrig, Timothy P
Abstract: Flualprazolam is a novel psychoactive substance in the benzodiazepine class that is increasing in prevalence in the USA. This study describes 19 cases of drivers stopped for impaired driving where flualprazolam was detected. This represents ∼9% of the total cases submitted to the Sedgwick County Regional Forensic Science Center toxicology laboratory between July 2019 and May 2020. Blood concentrations of flualprazolam ranged from 4 to 69 ng/mL, with mean and median concentrations of 20.9 ng/mL and 15 ng/mL, respectively. The increased prevalence in which laboratories are detecting flualprazolam along with the low concentrations necessary for pharmacological effects illustrates the importance of laboratories to remain vigilant in testing for novel psychoactive substances.